KAMPUNG KREATIF MELALUI INOVASI PENGOLAHAN BAWANG MERAH DALAM UPAYA MENINGKATKAN PEREKONOMIAN MASYARAKAT - Wardatus Syarifah (Universitas Al-Amien Prenduan, 2022)
Creative villages have the concept of favoring one particular product that is mass-produced, ranging from creativity in the fields of mural art, musical, tourism, to being creative in terms of producing products typical of the village. Creative village is one of the ideas to improve the community's economy. Sokobanah Tengah Village is the location for community empowerment activities. The majority of the population has a livelihood as farmers, because this village has a fairly large agricultural land. One of the potentials of Sokobanah Tengah village is onion which will improve the village economy through innovation in processing onion into products with high selling value. To achieve this goal, the author uses the Asset Based Community Development (ABCD) method. This method was developed from the assets owned by the village. With the ABCD method, the author creates a creative village program from the village's superior assets, namely the innovation of processing onion into products that have high economic value and quality. The result of this activity is to produce Pastel Bawang, Ticwang and Siwang products from processed onion which are well received by the village community, as well as receiving many orders from people within the village and outside the village.Â